Savings in Chile: What Went Right? - Felipe G. Morandé (Inter-American Development Bank, Office of the Chief Economist, 1996)
Some analysts rank Chile as the only Latin American economy that qualifies as a `take-off economy,` or development economy. In a sense, Chile`s enduring success and proved insulation from the `Tequila effect` are due to its high national savings. What has made Chile`s savings so high? What were some key policies implemented? Did the structural and liberalizing reforms of the late 1970s and 1980s have anything to do with it? This paper tries to empirically disentangle some of the puzzles with historical data that span the 1960-1995 period.
Keywords: 330